Anxiolytic and sedative activities of aqueous leaf extract of Dichrocephala integrifolia (Asteraceae) in mice. (24th December 2015) - Ketcha Wanda, Germain Jean Magloire; Djiogue, Sefirin; Gamo, Franklin Zemo; Ngitedem, Steve Guemnang; Njamen, Dieudonné
Abstract: Ethnopharmacological relevance: Dichrocephala integrifolia (Asteraceae) is commonly used in the folk medicine in Cameroon to treat various ailments including headaches, jaundice, filariasis, neuritis and children's night agitation. It is also known to have anxiolytic properties. Since there were no scientific data supporting the above claims, we therefore aimed to evaluate the anxiolytic and sedative effects of the aqueous leaf extract of D. integrifolia . Materials and methods: The extract used was obtained after maceration of leaves of D. integrifolia in water at room temperature. The anxiolytic effect was tested by the elevated plus-maze (EPM) and Open Field tests while the sedative effect was evaluated by the diazepam-induced sleep test. Results: D. integrifolia significantly induced an increase in the percentage of entries into open arms and a decrease in percentage of entries into closed arms at the dose of 22 mg/kg BW. The extract also induced a decrease of rearing and head dipping at the doses of 22 and 40 mg/kg BW during the EPM test. In addition, D. integrifolia extract induced a significant increase of crossing and time spent at the center of the experimental set at the dose of 40 mg/kg BW during the open field test. Lastly, D. integrifolia caused a significant reduction of the latency to sleep and an increase of total sleep time at the doses of 22 and 40 mg/kg BW in the diazepam-induced sleep test. Conclusion: The results obtained in this study suggest that the aqueous leaf extract of D. integrifolia is endowed with anxiolytic and sedative properties, which justify its traditional use. Graphical abstract: Highlights: Dichrocephala integripholia exhibits anxiolytic and sedative activities in mice. Anxiolytic properties are confirmed in the Open Field and Elevated plus-maze tests. D. integripholia may act on the benzodiazepines sites of GABA receptors. Reduction of the latency of sleep induced by diazepam and increased duration of sleep. Sedative properties may be related to components activating benzodiazepine and/or GABA receptors.